Asymmetric behavior of exchange rate pass-through in Thailand - Bala, Umar; Songsiengchai, Patchaya; Lee, Chin (Economics Bulletin, 2017)
The purpose of this paper is to examine the asymmetric behavior in the adjustment of exchange rate pass-through to consumer price index in Thailand. This research applies advanced threshold cointegration model proposed by Enders and Siklos (2001). Both the Threshold Autoregressive (TAR) and Momentum Threshold Autoregressive (MTAR) models result showed the evidence of cointegration in the non-zero threshold value. Furthermore, both models revealed that the adjustment towards long-run equilibrium are asymmetric. The adjustment during exchange rate depreciation significantly affect inflation, while the adjustment during exchange rate appreciation is not significant. This paper suggests that policy makers should have a different reaction in policy decision between the depreciation and appreciation of exchange rate pass-through to consumer price index.